Modification of Activated Carbon Norit Using Natural Antioxidant for Better Medicine - Gamgulu, Wahyuni (Agrikan Jurnal Agribisnis Perikanan, 2023)
Norit is one of drugs that is often used to cure diarrhea diseases due to its role as an adsorbent of viruses and bacteria. Its function can be improved through surface modification, such as antioxidant compounds from plant extracts. Two types of plants (rosella petals and green tea leaves) were extracted by using water solvent at ratio of 10 g/200 mL and 30 g/200 mL. Those extracts were used to modify 5 g of norit. The norit and the modified norit were characterized by FTIR spectrometry, while the extracts were characterized using UV-Vis spectrophotometry. Desorption test of the modifed norit was performed by immersing it in the HCl solition (pH 1). The desorpted antioxidant was analyzed using UV-Vis spectrophotometry. Results of the characterization indicated increasing of -C=O, -OH, C-O, and aromatic C=C aromatic on both norit modifications. UV-Vis spectra of the plant extract showed the maximum wavelength at 283 nm and 271 nm related to functional group of antioxydant. The antioxydant of the green tea modified norit was easily desorped at pH 1 than of rosella modified norit.